Seguridad del paciente y personal de enfermería especializado en quirófano - Cevallos Mejía, Carmen Elizabeth (2025)
This research paper addresses patient safety and the importance of specialised nursing staff in the operating theatre. The objective is to determine the benefits of having trained personnel to improve safety in this environment in Ecuador. The theoretical framework addresses the relevance of safety protocols and organisational culture as key elements to reduce risks and improve clinical outcomes. The methodology used is qualitative, non experimental and descriptive, based on direct observation and literatu re review, which allowed for the identification of deficiencies in the application of protocols and in the management of work related stress. The results reveal inconsistencies in adherence to safe practices, as well as a lack of specialised and consistent ly trained staff, which increases the risk of adverse events. The discussion highlights the need to strengthen the safety culture, continuous training and the implementation of more effective strategies to improve the surgical environment. In conclusion, i t is stressed that, despite technological advances, it is essential to restructure safety policies and improve staff deployment to reduce risks and ensure higher quality care in operating theatres.